Decolonizing educational relationships : practical approaches for higher and teacher education - Pirbhai-Illich, Fatima; Martin, Fran; Pete, Shauneen (Emerald Publishing Limited, 2023)
Due to the enduring legacy of the colonial, capitalist project, we have arguably entered an era of social, cultural, economic, and environmental collapse. There is a heightened awareness of a range of global issues including racism and xenophobia, economic and cultural protectionism, environmental degradation, and climate change - yet there appears to be a resistance to taking action that challenges the status quo, maintaining a way of life that continues to divide the world in unequal and inequitable ways, including in education. The complicity of westernized education in contributing to these issues has led calls to decolonize educational ideologies, structures, and practices. In response, the authors present a novel way of thinking and a robust foundation for de/colonizing educational relationships in Higher and Teacher Education, illustrated by examples of applications to practice. A hybrid style of writing weaves their own narratives into the text, drawing on their experiences in a range of educational settings.
Includes index.
Keywords: Educational sociology.; Teachers -- Training of.; Education, Higher.; Decolonization.; Education -- Educational Policy & Reform -- General.; Higher & further education, tertiary education.; elektronické knihy; electronic books